VACTERL association with double-chambered left ventricle: A rare occurrence - Abdulla Al-Farqani; Prashanth Panduranga; Salim Al-Maskari; Eapen Thomas (Wolters Kluwer Medknow Publications, 2013)
VACTERL association is a non-random association of birth defects of unknown etiology derived from structures of embryonic mesoderm. The common cardiac defects seen with VACTERL association are ventricular septal defects, atrial septal defects, and tetralogy of Fallot. We present a 2-year-old child with VACTERL association in whom we detected double-chambered left ventricle on transthoracic echocardiography.